Identidade de liderança: um estudo com os líderes estratégicos da Rede Marista - Cunha, Aline da (Universidade do Vale do Rio dos Sinos, 2017)
Organizations seek more and more leaders who identify themselves with their principles and reproduce the institution’s values in their daily practices. The Marist Network is an institution that stimulates the development of its leaders and identification with the charism of its founder. The objective of this study was to analyze the main characteristics that compose the leadership identity in the Marist Network, in the personal, relational and institutional dimensions, through a qualitative approach of exploratory nature, having as strategy the Case Study. The data collection was done through semi-structured interviews conducted with strategic leaders who work in the Marist Network projects, and the documentary research about the leadership trajectory of the founder of the institution.The data were treated by Content Analysis with a priori and emerging categories. Responding to the objectives of the research, it was identified the main challenges and changes faced by Marist leaderships; the way in which the founder's principles express themselves in today's leadership identity and it was presented the fundamental elements that must be considered in a Marist Leadership Training Program. The construction of leadership identity occurs through the self development and the established influences in relations with people, with groups and with the institution.
Keywords: Identidade de liderança; Instituição Marista; Programa de desenvolvimento de lideranças; Leadership identity; Marista institution; Leadership and development program; ACCNPQ::Ciências Humanas::Educação